Comparison of complementary and alternative medicine use: reasons and motivations between two tertiary children's hospitals. Issue 2 (15th September 2005) - Cincotta, D R; Crawford, N W; Lim, A; Cranswick, N E; Skull, S; South, M; Powell, C V E
Abstract : Aims: To compare prevalence, reasons, motivations, initiation, perceived helpfulness, and communication of complementary and alternative medicine (CAM) use between two tertiary children's hospitals. Methodology: A study, using a face-to-face questionnaire, of 500 children attending the University Hospital of Wales, Cardiff, UK was compared to an identical study of 503 children attending the Royal Children's Hospital, Melbourne, Australia. Results: One year CAM use in Cardiff was lower than Melbourne (41% v 51%; OR = 0.67, 95% CI 0.52–0.85), reflected in non-medicinal use (OR = 0.41, 95% CI 0.29–0.58) and general paediatric outpatients (OR = 0.38, 95% CI 0.21–0.67). Compared to Melbourne, factors associated with lower CAM use in Cardiff included families born locally (father: OR = 0.58, 95% CI 0.44–0.77) or non-tertiary educated parents (mother: OR = 0.54, 95% CI 0.38–0.77). Cardiff participants used less vitamin C (OR = 0.31, 95% CI 0.18–0.51) and herbs (OR = 0.49, 95% CI 0.34–0.71), attended less chiropractors (OR = 0.25, 95% CI 0.06–0.37) and naturopaths (OR = 0.08, 95% CI 0.02–0.33), but saw more reflexologists (OR = 3.33, 95% CI 1.08–10.29). In Cardiff, CAM was more popular for relaxation (OR = 1.92, 95% CI 1.03–3.57) but less for colds/coughs (OR = 0.4, 95% CI 0.27–0.73). Most CAM was self-initiated (by parent) in Cardiff and Melbourne (74% v 70%), but Cardiff CAM users perceived it less helpful (OR = 0.46, 95% CI 0.31–0.68). Non-disclosure of CAM use was high in Cardiff and Melbourne (66% v 63%); likewise few doctors/nurses documented recent medicinal CAM use in inpatient notes (0/21 v 2/22). Conclusions: The differences in CAM use may reflect variation in sociocultural factors influencing reasons, motivations, attitudes, and availability. The regional variation in use and poor communication highlights the importance of local policy development.